2020
DOI: 10.2147/cmar.s285367
|View full text |Cite
|
Sign up to set email alerts
|

KIF14 and KIF23 Promote Cell Proliferation and Chemoresistance in HCC Cells, and Predict Worse Prognosis of Patients with HCC

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most common human malignant tumors. The prognosis of HCC patients is still unsatisfying. In this study, we performed the integrated bioinformatics analysis to identify potential biomarkers and biological pathways in HCC. Methods Gene expression profiles were obtained from the Gene Expression Omnibus database (GSE55048, GSE55758, and GSE56545) for the screening of the common differentially expressed genes (DEGs) bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…RRM2 promotes the occurrence of cell resistance by activating the EGFR/AKT pathway, while lncRNA can up-regulate RRM2 by binding to and inhibiting the expression of miR-139-5p, which is consistent with our research [50]. KIF23 is related to the worse prognosis of HCC patients and has a promoting effect on the proliferation and chemoresistance of HCC cells [51]. TXNIP has long been recognized as a potential tumor suppressor gene that inhibits cell growth and is involved in stress response, REDOX regulation, and cell proliferation [52,53].…”
Section: Plos Onesupporting
confidence: 91%
“…RRM2 promotes the occurrence of cell resistance by activating the EGFR/AKT pathway, while lncRNA can up-regulate RRM2 by binding to and inhibiting the expression of miR-139-5p, which is consistent with our research [50]. KIF23 is related to the worse prognosis of HCC patients and has a promoting effect on the proliferation and chemoresistance of HCC cells [51]. TXNIP has long been recognized as a potential tumor suppressor gene that inhibits cell growth and is involved in stress response, REDOX regulation, and cell proliferation [52,53].…”
Section: Plos Onesupporting
confidence: 91%
“…Recently, accumulating studies focused on the molecular mechanisms of cisplatin chemoresistance emerged. For example, the kinesin superfamily (KIF) members KIF14 and KIF23 have been shown to promote cisplatin-resistance in HCC (Cheng et al, 2020). Branched-chain amino acid transaminase 1 (BCAT1) (Luo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The downstream of DEPDC1B, KIF23, is a member of kinesin motor protein involved in the regulation of cytokinesis and acts as an important regulator in cancer biology [ 33 ]. In this paper, similar to DEPDC1B, KIF23 expression was also upregulated in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Like DEPDC1B, KIF23 was overexpressed in various cancers, such as pancreatic cancer, breast cancer and primary lung cancer [ 34–36 ]. In addition, a study revealed that KIF23 expression was significantly upregulated in HCC cells, and the knockdown of KIF23 inhibited the proliferation of HCC cells by affecting the cell cycle [ 33 ].…”
Section: Discussionmentioning
confidence: 99%